2015
DOI: 10.1177/1463949115585442
|View full text |Cite
|
Sign up to set email alerts
|

Toward broader perspectives of young children’s mathematics: Recognizing and comparing Olivia’s beliefs and activity

Abstract: Little research exists on young children's beliefs about mathematics, and current research perspectives on early mathematical activity may overlook a great deal of young children's sophisticated mathematical thinking. We argue this is attributable, in part, to a need for a broader view of what mathematics is, including cultural practices that are mathematical. Thus, this study investigated a young child's mathematical activity and beliefs prior to school using a framework reflecting a view of mathematics as cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Evidence from our review strongly suggests that interviews are the preferred-or at least the most common-strategy to listen to children's voices. The most prevalent types of interviews found in our review were semi-structured (Fekonja-Peklaj and Marjanovič-Umek, 2015;Koller and San Juan, 2015;Northard et al, 2015;Reunamo et al, 2015;O'Rourke, O'Farrelly, Booth and Doyle, 2017;Wernet and Nurnberger-Haag, 2015;Wu, 2015), and only two studies used structured interviews (Correia and Aguiar, 2017;Kotaman and Tekin, 2017). It is interesting to note that while interviews were the main strategy to listen to children's voices, we found a great variation in their use with regards to conditions, circumstances and material used to elicit children's views.…”
Section: Interviewsmentioning
confidence: 90%
See 2 more Smart Citations
“…Evidence from our review strongly suggests that interviews are the preferred-or at least the most common-strategy to listen to children's voices. The most prevalent types of interviews found in our review were semi-structured (Fekonja-Peklaj and Marjanovič-Umek, 2015;Koller and San Juan, 2015;Northard et al, 2015;Reunamo et al, 2015;O'Rourke, O'Farrelly, Booth and Doyle, 2017;Wernet and Nurnberger-Haag, 2015;Wu, 2015), and only two studies used structured interviews (Correia and Aguiar, 2017;Kotaman and Tekin, 2017). It is interesting to note that while interviews were the main strategy to listen to children's voices, we found a great variation in their use with regards to conditions, circumstances and material used to elicit children's views.…”
Section: Interviewsmentioning
confidence: 90%
“…These observations lasted 3 months in Hong Kong and 42 days in Germany. On the other hand, in a case study reported by Wernet and Nurnberger-Haag's (2015) the authors observed a child aged 3 years and 9 months during two consecutive weeks at her home.…”
Section: Observationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Indeed, there were examples in which the approach appeared to have been designed for power differentials, e.g., by seating the child opposite the researcher in an environment other than their own educational environment (e.g., Aykol 2020), and we did not find evidence of discussion with participants around the degree of power sharing within the studies (Lundy and McEvoy, 2009). In other instances, researchers relied on observations to obtain spontaneous children's ideas about a particular topic (e.g., Fekonja-Peklaj and Marjanovič-Umek 2015; Reunamo et al 2015;Sisson, Whitington, and Shin 2020;Wernet and, Nurnberger-Haag 2015). Arguably, the information obtained through this medium does not necessarily reflect children's perspectives, but rather it reflects the interpretative process of what researchers observe (Spradley 2016).…”
Section: Data Collection Methods Used By Studies Aiming To Listen To ...mentioning
confidence: 99%
“…In accurate counting book types, who is portrayed as doing simple or more complex mathematics? This typology could provide a conceptual tool for analyzing the children's books in relation to Critical Theory (e.g., Taylor et al, 2009) or other theoretical approaches that address identity or other perspectives on social justice to ensure all learners meet their potential and see themselves as doers of mathematics (Wernet & Nurnberger-Haag, 2015).…”
Section: Contribute To Social Justice In Terms Of Socioeconomic Statusmentioning
confidence: 99%